A comprehensive approach ecuadorian higher education - Vásquez Martínez, Nelly (Revista Universidad de Guayaquil, 2012)
Higher education institutions are guiding the life of a country, must graduate from their classroomswho govern their people, and recognize the important role they playwithin the social environment,enrumbando science and technology to make it available of the community. A nation is what youruniversity.Today in Ecuador teaching is undergoing a profound process of academic innovation, and how tocontributetoreorienteducationtowardssignificantdevelopment,comingintoforcetheLawonHigher Education (LOES). Concern about the whole education is a priority of state, and we must buildtogether the conditions for the near future to improve the quality of training processes and a realeducationsystem inthecountry
Keywords: University; Science; Technology; Education; Society; State